Papaya Juice Treatment Increases Body Weight and Decreases Urea Levels in Lead acetate-exposed Wistar Rats - Purlinda, Devi Etivia; Putri, Nanik Aryani; Widodo, Widodo; Kahar, Fitriani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Lead (Pb) exposure poses significant health risks due to its non-degradable nature and profound toxicity, causes oxidative stress and organ damage, particularly targeting the kidneys. Urea nitrogen levels rise as a result of decreased renal filtration rate and urea excretion. This study investigates the potential of papaya juice, rich in flavonoids, vitamins C, E, and beta-carotene, as a protective agent against Pb-induced nephrotoxicity. A Completely Randomized Design experiment was conducted, involving six treatment groups of Wistar rats. Papaya juice was administered at doses of 3.6, 7.2, and 14.4 g/200g body weight (BW) to Groups P1, P2, and P3, respectively, prior to exposure to 50 mg/kg BW of lead acetate. Group PC received vitamin E (400 IU/kg BW) and lead acetate, while Group NC was exposed to lead acetate alone. Group NT served as the control. Following a 28-day treatment period, the P3 group exhibited the most significant improvements, with a notable increase in body weight (22.50 grams) and a substantial decrease in urea nitrogen levels (18.24 mg/dl). These findings underscore the efficacy of papaya juice treatment in mitigating Pb-induced nephrotoxicity, suggesting a potential therapeutic regimen for alleviating lead toxicity in exposed populations. Eventually, the optimal dosing for papaya juice treatment, either at 14.4 g per 200 g body weight for rats or consumption of one medium-sized papaya for humans, yields compelling benefits. This regimen demonstrates significant efficacy in increasing body weight and lowering serum urea levels in rats subjected to Pb acetate exposure.